MXene: An emerging two-dimensional layered material for removal of radioactive pollutants - Hwang, Seung Kyu; Kang, Sung-Min; Rethinasabapathy, Muruganantham; Roh, Changhyun; Huh, Yun Suk (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Exclusively focusing on 2D layered MXenes as promising radionuclides adsorbents.•Discusses state-of-the-art research on 238U, 232Th, 137Cs, 90Sr, and 133Ba removal.•Discusses the structure, synthesis, and properties of MXenes.•Discusses ion-exchange, inner sphere complexation in radionuclide adsorption.•Discusses MXenes challenges and research directions for environmental remediation. MXenes have very recently emerged as an intriguing family of graphene-like two-dimensional (2D) layer-structured transition metal carbides and/or nitrides with a high specific surface area, a large interlayer spacing, hydrophilicity, and abundant highly active surface sites, and they have found a niche in environmental remediation, as materials capable of efficiently removing and sequestering heavy metals, dyes, and radioactive nuclides. With exceptional surface tunable chemical compatibility and compositional flexibility, MXenes are resistant to radiation-induced damage and show high chemical compatibility and excellent thermal stability. They are thought to have the potential to serve as ideal adsorbents for a plethora of radionuclides such as uranium (238U), thorium (232Th), cesium (137Cs), and strontium (90Sr) with respect to technology and the economy. In this article, we comprehensively review state-of-the-art research progress on and the promising potential of MXenes as an adsorbent for the removal of radioactive nuclides from the environment. First, we discuss the structure, synthesis, intercalation/delamination and properties of MXenes. Subsequently, we emphasize their radionuclide removal applications. Finally, we present an outlook on the current challenges in the use of MXene materials for the adsorptive remediation of radionuclides and outline future opportunities for these materials. This article presents a timely and systematic review of MXenes as efficient and cost-effective radionuclide adsorbents. Furthermore, it highlights the main challenges in their use for environmental remediation and provides possible research directions.